Familial Aggregation and Heritability of Myopia: A Local Population Survey in Shanxi, China - Qin Wang; Hao-Yu Bi; Chun-Fang Wang (Journal of Tropical Medicine)
Purpose. To further determine the roles of environmental and genetic factors in the development of myopia, a comprehensive survey was performed. The guidance for myopia-susceptible people is established which might help prevent or delay the onset and development of myopia. Methods. 1,852 students were recruited using the multistage sampling approach from the Gaoping county in Shanxi. The refractive status of students was examined using an autorefractometer, and the refractive status of students’ first-degree relatives was collected using a well-designed questionnaire. Family aggregation of myopia was analyzed according to the myopic status of the students (nonmyopic or myopic group). The prevalence and heritability of myopia in students and their first-degree relatives were further explored by subdividing into mild, moderate, and high myopia groups. Significance analysis among each group was performed by the χ2 test using SPSS 25.0 software. Falconer’s method was used to calculate the inheritability of myopia. Results. A total of 1,852 subjects were recruited in this study, and 1,813 subjects were finally included. The family aggregation of myopia in the myopic student group (34.7%) was significantly higher than that in the nonmyopic group (8.5%). The prevalence of mild, moderate, and high myopia in children (students and siblings) was higher than that in their parents. The rate of high myopia (6.33%) was significantly higher among students with one or both myopic parents than those without myopic parents (3.85%). The heritability of mild, moderate, and high myopia among parents-offspring was 3.72%, 20.47%, and 48.00%, respectively. The heritability of mild, moderate, and high myopia among siblings was 17.50%, 86.09%, and 78.75%, which is significantly higher than that among parents-offspring. In addition to genetic factors, extensive near-work time, higher education pressure, and minimal outdoor activities contribute significantly to mild and moderate myopia. Conclusions. Myopia is of high risk due to familial aggregation. Students with a family history of myopia are more likely to have high myopia than those without family history. The occurrence and development of high myopia are affected by both the genetic and environmental factors, which could either weaken or strengthen myopia. Therefore, students with a family history of myopia should pay close attention to their eye health to avoid the occurrence of myopia and the deepening of diopter, which may lead to high myopia and its related complications.